Justice and Violence : Political Violence, Pacifism and Cultural Transformation - Nelson, Eric; Eickelmann, Allan; Lansford, Tom (Ethics and global politics., 2019)
Originally published in 2003. Justice and Violence brings together a fascinating and varied volume that focuses on the ethics of both political violence and pacifism. Incorporating historical, geopolitical and cultural case studies, it takes a unique look at comparative analyses of these two phenomena and contending world views. The volume is a 'must read' for political scientists, ethicists, historians, sociologists, anthropologists and policy analysts. As we move deeper into the twenty-first century, the contradictory and conflicting forces of globalization and cultural fragmentation make it increasingly crucial to give serious consideration to the issues raised here.